PS-C11-7: STUDY OF 24-HOUR CUFF-LESS, CONTINUOUS AND NON-INVASIVE BLOOD PRESSURE MEASUREMENT IN 100 CHILDREN AND ADOLESCENTS SHOWS CLINICAL VALIDITY. (January 2023) - Bothe, Tomas Lucca; Wette, Martin Hulpke; Patzak, Andreas; Pilz, Niklas
Abstract : Objective: The reduction of discomfort caused by conventional, cuff-based blood pressure (BP) determination is a promising trend in ambulatory, cuff-less BP measurement devices. Mitigating these discomforts is especially desirable when performing measurement in children. In this study we want to assess the clinical validity of a cuff-less BP measurement device for 24-hour measurements in children and adolescents. Methods: We compared the simultaneously retrieved BP data of the cuff-less SOMNOtouch(TM) NIBP and the cuff-based Mobil-O-Graph® in 24-hour use in 100 children in the range from 5–17 years old. Results: A total of 1245 valid measurement pairs showed a mean deviation of 1.08 mmHg (limits of agreement: 24.10 / -21.93) for systolic and 3.32 mmHg (limits of agreement: 25.13 / -18.48) for diastolic BP values. Patient specific difference of means was within 15 mmHg in 95.6% (systolic BP) and 92.3% (diastolic BP) patients. 24.3% of nocturnal cuff inflations led to determinable, BP relevant arousal reactions. Conclusion: The SOMNOtouch(TM) NIBP showed desirable measurement accuracy over a broad spectrum 24-hour, ambulatory BP measurements in children and adolescents. Cuff-less blood pressure measurement relieves the issue of nocturnal arousal reactions which showed to be frequently induced by cuff-based measurements. We encourage the use of this cuff-less BP measurement device in everyday practice, driven by this clear indication of clinical validity and benefits in patient comfort.